Member - Chrysostomou, Christis (My University, 2026)
Appointed by the Ministry of Interior as the representative of Cyprus to the Eurocodes National Correspondents Group. This is a 28 member counselling body to the European Commission that convenes in Brussels twice a year and covers issues concerning the development and adoption of Eurocodes in the Member States of the European Union. The appointment is valid to date.